Exploring Past Tense Usage in EFL Hospitality Students’ Narrative Essays - Stefanus Angga B. Prima; Dang Arif Hartono; Douwes Lasmana (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
This study attempts to analyze the differences of morphological features used by hospitality students in indicating tenses while writing narrative essays. Four participants of different CEFR levels enrolled in a private university in Jakarta were asked to write short essays of a story how they ended up choosing hospitality major. The method utilized discourse hypothesis, in which the morphological features indicating past, non-past, and no verb were categorized and counted. The results show that the most advanced students produce the most variety of tenses, while the lowest produce the least variety of tenses. The results indicate further interesting discussion on how interlanguage paradigm may take more important role in pedagogical approach of EFL classes for vocational students.